Comparative characteristics of pneumonia caused by Mycoplasma pneumoniae in children - S. L. Bevza; O. V. Molochkova; O. B. Kovalev; O. V. Shamsheva; A. A. Sakharova; A. A. Korsunsky; M. V. Parshina; K. G. Burkova; E. A. Labuzova; N. V. Sokolova (Журнал инфектологии)
The urgency of the problem of community-acquired pneumonia in children is due to the high incidence rate. In the etiological structure of bacterial pneumonia, Streptococcus pneumoniae and Mycoplasma pneumonia (Mp) prevail.Purpose: to identify clinical, laboratory and instrumental features of mycoplasmal pneumonia in children.Materials and methods. A retrospective,  single-center cohort study  of  266  case  histories  of  children  aged  4 months to 17 years who were in Children’s City Clinical Hospital No. 9 in 2019 with a referral diagnosis of pneumonia was carried out. To verify the diagnosis of pneumonia, the method of chest X-ray was used, for the etiological diagnosis, the method of PCR swabs from the nasopharynx, ELISA for the detection of antibodies of the IgM and IgG classes was used. Results. The diagnosis  of  pneumonia was confirmed in 190 children. The diagnosis of pneumonia caused by M. pneumoniae (MpP) was established in 76 (40%) children, they made up the 1st group. The remaining 114 (60%) children with community-acquired pneumonia of another etiology (CAP) made up the 2nd group – comparisons. The diagnosis of MpP was confirmed in 46 (60.5%) children by the detection of IgM, in 12 (15.8%) by the detection of Mp genetic material, and in  18  (23.7%) by positive both IgM and PCR. The median age of children in the group with MpP was 9.6 years, in the comparison group – 4 years (p<0.01). Significantly more often MpP occurs in children aged 11–17 years (p < 0.01), and CAP – up to 7 years (p < 0.01). With MpP, catarrhal phenomena in the form of hyperemia of the oropharynx, nasal congestion, and unproductive cough are observed less frequently than with CAP. With MpP, rales in the lungs are heard more often than with CAP, they are significantly more often wet (p<0.01). Respiratory failure and dyspnea are less common in MpP than in CAP. Bilateral lesions and lesions of the upper lobe of the lungs are more often detected in MpP, and in CAP – right-sided lesions. In the general blood test, leukocytosis, incl. above 15  thousand/µl,  as well as leukopenia below 4 thousand/µl were significantly more frequent in the group of patients with CAP (p<0.01). Conclusion. No clear clinical and laboratory criteria for mycoplasmal etiology of pneumonia have been obtained, which dictates the need for laboratory confirmation for the choice of therapy tactics.